THE IMPACT OF HRM PRACTICES ON SERVICE QUALITY IN CUSTOMER-FACING BUSINESSES - Salem Alqarni (International Journal for Quality Research)
This research analyses the impact of HRM practices on service quality in customer-facing businesses. A systematic review was conducted using Google Scholar as the search engine, and search terms such as "HRM practices", "Service quality", and "Customer-facing business" were used to identify relevant papers. The inclusion and exclusion criteria were documented using the PRISMA flow diagram, and a total of 30 papers were included in the review. The findings indicate that HR practices focused on equipping employees with social skills in customer-facing encounters have a positive impact on customer perceptions of quality and satisfaction. However, certain HR and external factors may moderate this relationship. These trends were observed across all sectors of organisations. The study also found that the majority of papers were published between 2009-2014, with a recent increase in publications. The UK and the USA are the top countries as data sources, and most papers were research-based and used survey methods. Limited use of theories was also observed in the included reviews. The research also attempts to use the average number of citations per year as a measure of paper quality, acknowledging certain limitations in this approach. Overall, the findings highlight the importance of HRM practices in improving service quality in customer-facing businesses and the need for more research in this area.